MULTI-CRITERIA MEASUREMENT OF AGRI-ENVIRONMENTAL PERFORMANCE IN EUROPEAN UNION COUNTRIES - Marković, Milan; Stanković, Jelena; Marjanović, Ivana; Krstić, Bojan; Papathanasiou, Jason (Economics of Agriculture, 2024)
The purpose of the paper is to assess the agri-environmental situation in the European Union at the national level. To realize that goal, a multi-criteria analysis of indicators from the official European database was used. The results of the ranking show that Portugal, Estonia, and Ireland are at the top according to agri-environmental performance, while the worst ranked countries are Malta, the Netherlands, Slovenia, and Cyprus. The common agricultural policy of the European Union must be designed to improve the position of certain countries, based on the experience and sustainable agricultural practices of the leading countries in this area, considering the obtained research results. This study can contribute to the creators of agri-environmental policies in the preparation of the future strategy of the agricultural development of the European Union countries.